2022
DOI: 10.3389/fphys.2022.979121
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-mRNA modules involved in goat rumen development: Insights from genome-wide transcriptome profiling

Abstract: The rumen is an essential digestive and absorption organ of ruminants. During fetal life, lactation, and post-weaning period, goat rumen undergoes drastic morphological and metabolic-functional changes triggered by potential regulated genes and non-coding RNA molecules. As the essential regulatory factors, long non-coding RNAs (lncRNAs) have vital functions in various biological activities. However, their roles during rumen development are still poorly explored in ruminants. To explore the genome-wide expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Based on multi-omics studies, the mechanism of host-microbial interaction and its role in regulating rumen development in ruminants has been explored through the interaction between the early microbiome and the host transcriptome [16]. Zhong et al found that cis and trans target genes of DE lncRNAs in four different developmental stages of goat rumen epithelium were mainly enriched in pathways related to the growth and metabolism of rumen cells, which provided a basis for the study of genetic regulation and molecular mechanism of ruminal development in ruminants [17]. Lu et al explored the hypoxia adaptability of Tibetan sheep by studying lncRNA in the lung tissue of highaltitude and low-altitude Hu sheep [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on multi-omics studies, the mechanism of host-microbial interaction and its role in regulating rumen development in ruminants has been explored through the interaction between the early microbiome and the host transcriptome [16]. Zhong et al found that cis and trans target genes of DE lncRNAs in four different developmental stages of goat rumen epithelium were mainly enriched in pathways related to the growth and metabolism of rumen cells, which provided a basis for the study of genetic regulation and molecular mechanism of ruminal development in ruminants [17]. Lu et al explored the hypoxia adaptability of Tibetan sheep by studying lncRNA in the lung tissue of highaltitude and low-altitude Hu sheep [18].…”
Section: Introductionmentioning
confidence: 99%